Evaluation of clinician interaction with alerts to enhance performance of the tele-critical care medical environment. (July 2020) - Kaur, Dhamanpreet; Panos, Ralph J.; Badawi, Omar; Bapat, Sanika S.; Wang, Li; Gupta, Amar
Highlights: Alarm fatigue is a well-known issue impeding bedside patient care in the ICU. High frequencies of clinically irrelevant alarms aggravate alarm fatigue. Tele-Critical Care systems show frequent, repetitive, and potentially unnecessary alerts. Frequency and clinician choice of reactivation time vary by alert type. Customizing limit alert settings could reduce cognitive workload, and thus alert fatigue. Abstract: Objective: Identify opportunities to improve the interaction between clinicians and Tele-Critical Care (Tele-CC) programs through an analysis of alert occurrence and reactivation in a specific Tele-CC application. Materials and Methods: Data were collected automatically through the Philips eCaremanager® software system used at multiple hospitals in the Avera health system. We evaluated the distribution of alerts per patient, frequency of alert types, time between consecutive alerts, and Tele-CC clinician choice of alert reactivation times. Results: Each patient generated an average of 79.8 alerts during their ICU stay (median 31.0; 25th – 75th percentile 10.0–89.0) with 46.4 for blood pressure and 38.4 for oxygenation. The most frequent alerts for continuous physiological parameters were: MAP limit (28.9 %), O2 /RR (26.4 %), MAP trend (16.5 %), HR trend (12.1 %), and HR limit (11.3 %). The median time between consecutive alerts for one parameter was less than 10 min for 86 % of patients. Tele-CC providers responded to all alert types with immediate reactivation 47–88 % of the time. Limit alerts had longer reactivation times than their trend alert counterparts (p-value < .001). Conclusions: The alert type specific differences in frequency, time occurrence and provider choice of reactivation time provide insight into how clinicians interact with the Tele-CC system. Systems engineering enhancements to Tele-CC software algorithms may reduce alert burden and thereby decrease clinicians' cognitive workload for alert assessment. Further study of Tele-CC alert generation, alert presentation to clinicians, and the clinicians' options to respond to these alerts may reduce provider workload, minimize alert desensitization, and optimize the ability of Tele-CC clinicians to provide efficient and timely critical care management.